2005
DOI: 10.1159/000086335
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of CXCR3-Expressing Eosinophils and Increased Concentration of Its Ligands (IP10 and Mig) in Bronchoalveolar Lavage Fluid of Patients with Chronic Eosinophilic Pneumonia

Abstract: Background: Since human peripheral eosinophils have been shown to migrate to the CXC chemokine receptor 3 (CXCR3) ligands IFN-γ-inducible protein 10 (IP10) and monokine induced by IFN-γ (Mig), this confirms that CXCR3 is functionally expressed on these cells. IP10 expression has been shown to be increased in the airways of asthmatics. Eosinophil accumulations are found in bronchoalveolar lavage fluid (BALF) from patients with chronic eosinophilic pneumonia (CEP). To examine the contribution of IP10 and Mig in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
2
21
0
3
Order By: Relevance
“…In both cases correlations were found to the absolute number of lymphocytes in the BALF. Similarly, Katoh et al [17] found elevated BALF levels of IP10 and MIG in patients with chronic eosinophilic pneumonitis. Furthermore, other investigators [15], [18] have found associations between IP10 and interstitial lung diseases.…”
Section: Discussionmentioning
confidence: 82%
“…In both cases correlations were found to the absolute number of lymphocytes in the BALF. Similarly, Katoh et al [17] found elevated BALF levels of IP10 and MIG in patients with chronic eosinophilic pneumonitis. Furthermore, other investigators [15], [18] have found associations between IP10 and interstitial lung diseases.…”
Section: Discussionmentioning
confidence: 82%
“…Several chemokines are also present in BAL fluid samples, including CCL17 and CCL22, the chemokine ligands of the receptor CCR4, suggesting that T cell recruitment may be an important factor in the pathophysiology of CEP (74,114). In addition, CXCL9, CXCL10, CCL5 (RANTES), CCL11 (eotaxin-1), CCL2, and CCL4 have also been observed to be elevated in CEP (73,75,89,186). Other immune mediators, such as tryptase, prostaglandins, and soluble ADAM8, have been detected to be elevated in the BAL fluid of CEP patients as well (7,109,132).…”
Section: Cepmentioning
confidence: 99%
“…For example, Liu et al reported that eosinophils in the airway express more CXCR3 and less CCR3 than those in peripheral blood [36]. Katoh et al found higher ratios of CXCR3-expressing eosinophils in BALF than in peripheral blood [37]. Nagase et al reported that less CCR3 is expressed by eosinophils in BALF than in peripheral blood [38].…”
Section: Discussionmentioning
confidence: 99%